PENGARUH FAKTOR PENDAPATAN TERHADAP PERMINTAAN DAGING SAPI DI KOTA PALU - Maksum, Haerani (FAPETKAN UNTAD, 2014)
The research was carried out to determine the income influence of the beefdemandÂ as well as the relationship between income and beef demand for three months.The methods used in this study were survey and interview. Collected data consisted of primary and secondary data. Research location gradually determined by multistage random sampling technique, while the determination ofÂ sampling respondents was by systematic sampling technique.The analysis modelswere Cobb Douglas multiple regression analysis for analyzing the income effect on the beef demand, and correlation analysis for determining the relationship between income andbeef demand.The results showed that the income affects the beef demand, and there was a close relationship between the income and beef demand. The increasedincomeas much as Rp. 154,290.13, - would increase the beef demand as much as 732,312.85 kg. Keywords : Income, Demand , Beef.